Performance analysis practice within Olympic and Paralympic sports: A comparison of coach and analyst experiences - Nicholls, S. B.; James, N.; Wells, J.; Parmar, N. (International Journal of Performance Analysis in Sport, 2022)
Concordance between 18 coaches (mean performance analysis experience: 8.3 ± 4.8 years) and 23 performance analysts (mean: 6.4 ± 4.1 years) regarding their performance analysis delivery within applied Olympic and Paralympic environments was investigated using survey-based methods. There was clear agreement on the provision, importance and need for full video. The majority of analysts (73.9%) provided profiling often or all of the time, whereas only one third of coaches felt that this was the required amount. Coaches not only agreed that coaching philosophy was the main factor directing analysis but also emphasised that training goals, level or age of athlete and discussions with athletes were influencers, far more than the analysts realised. A potential barrier for better communication was time, highlighted by all analysts as a major factor impacting their role. The majority of analysts (87%) attempted to provide feedback to athletes within one hour of performance, often or all the time. Coaches expressed a similar philosophy but were far more likely to want to provide feedback at later times. These findings should be utilised by analysts and coaches to review practice, identify gaps within practice and highlight areas for development.